Differences in erythrocyte phospholipid membrane long-chain polyunsaturated fatty acids and the prevalence of fatty acid desaturase genotype among African Americans and European Americans. (January 2021) - Rifkin, SB; Shrubsole, MJ; Cai, Q; Smalley, WE; Ness, RM; Swift, LL; Milne, G; Zheng, W; Murff, HJ
Highlights: African Americans were more likely to be homozygous for the G allele at rs174537 compared to European Americans (81% vs 43%), which is associated with higher arachidonic acid (AA) conversion. African Americans on average had higher concentrations of linoleic acid (LA), AA, decosahexaenoic acid (DHA), total n-6 polyunsaturated fatty acid (PUFAs) levels and eicosapentaenoic acid (EPA), while homozygous GG and GT had higher mean membrane concentrations of AA, di-homo-γ-linolenic acid (DGLA), DHA, total n-3 PUFA and AA to DGLA ratio compared to homozygous TT. Further cohort studies should evaluate if differences in rs174537 genotype and resulting differences in PUFAs might be related to some of the well-described health disparities seen between African Americans and European Americans. Abstract: Numerous studies have reported an association between genetic variants in fatty acid desaturases (FADS1 and FADS2) and plasma or erythrocyte long chain polyunsaturated fatty acid (PUFA) levels. Increased levels of n-6 PUFAs have been associated with inflammation and several chronic diseases, including diabetes and cancer. We hypothesized that genetic variants of FADS that more efficiently convert precursor n-6 PUFA to arachidonic acid (AA) may explain the higher burden of chronic diseases observed in African Americans. To test this hypothesis, we measured the level of n-6 and n-3 PUFAs in erythrocyte membrane phospholipids and genotyped the rs174537 FADS variants associated with higher AA conversion among African American and European American populations. We included data from 1, 733 individuals who participated in the Tennessee Colorectal Polyp Study, a large colonoscopy-based case-control study. Erythrocyte membrane PUFA percentages were measured using gas chromatography. Generalized linear models were used to estimate association of race and genotype on erythrocyte phospholipid membrane PUFA levels while controlling for self-reported dietary intake. We found that African Americans have higher levels of AA and a higher prevalence of GG allele compared to whites, 81% vs 43%, respectively. Homozygous GG genotype was negatively associated with precursor PUFAs (linoleic [LA], di-homo-γ-linolenic [DGLA]), positively associated with both product PUFA (AA, docosahexaenoic acid [DHA]), product to precursor ratio (AA to DGLA), an indirect measure of FADs efficiency and increased urinary isoprostane F2 (F2-IsoP) and isoprostane F3 (F3-IsoP), markers of oxidative stress. Increased consumption of n-6 PUFA and LA resulting in increased AA and subsequent inflammation may be fueling increased prevalence of chronic diseases especially in African descent.